Novel and known genetic variants for male breast cancer risk at 8q24.21, 9p21.3, 11q13.3 and 14q24.1: Results from a multicenter study in Italy. Issue 16 (November 2015) - Silvestri, Valentina; Rizzolo, Piera; Scarnò, Marco; Chillemi, Giovanni; Navazio, Anna Sara; Valentini, Virginia; Zelli, Veronica; Zanna, Ines; Saieva, Calogero; Masala, Giovanna; Bianchi, Simonetta; Manoukian, Siranoush; et al.
Abstract Increasing evidence indicates that common genetic variants may contribute to the heritable risk of breast cancer (BC). In this study, we investigated whether single nucleotide polymorphisms (SNPs), within the 8q24.21 multi-cancer susceptibility region and within BC-associated loci widespread in the genome, may influence the risk of BC in men, and whether they may be associated with specific clinical-pathologic characteristics of male BC (MBC). In the frame of the ongoing Italian Multicenter Study on MBC, we performed a case-control study on 386 MBC cases, including 50 BRCA1/2 mutation carriers, and 1105 healthy male controls, including 197 unaffected BRCA1/2 mutation carriers. All 1491 subjects were genotyped by Sequenom iPLEX technology for a total of 29 susceptibility SNPs. By logistic regression models, we found a significant association with MBC risk for five SNPs: rs1562430 (p = 0.002) and rs445114 (p = 0.026) both within the 8q24.21 region; rs1011970/9p21.3 (p = 0.011), rs614367/11q13.3 (p = 0.016) and rs1314913/14q24.1 (p < 0.0001). Differences in the distribution of rs614367/11q13.3 genotypes according to oestrogen receptor (ER) status (p = 0.006), and of rs1011970/9p21.3 genotypes according to human epidermal growth factor receptor 2 (HER2) status (p = 0.002) emerged. Association of rs1011970/9p21.3 risk genotype with HER2+ MBC was confirmed by a multivariate analysis. rs1314913/14q24.1 was associated with increased MBC risk in analyses restricted to male BRCA1/2 mutation carriers (p = 0.041). In conclusion, we provided the first evidence that the 8q24.21 region is associated with MBC risk. Furthermore, we showed that the SNPs rs1562430/8q24.21 and rs1314913/14q24.1 strongly influence BC risk in men and suggested that the SNP rs1314913/14q24.1 may act as a risk modifier locus in male BRCA1/2 mutation carriers.